Visual core description of IODP Hole 389-M0098A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Collection of visual core description (VCD) sheets (hand drawn originals) and digital lithostratigraphic logs from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). VCD was performed on unsampled archive halves of split core sections directly after line scan imaging, during the onshore phase of expedition 389, which took place between 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. The lithology of each core section is represented on the hand drawn VCDs by graphic patterns next to the line scan image of the archive-half core section. Further, a wide variety of features that characterize the sediment are indicated in additional columns. The information from the hand-drawn VCD sheets was then transferred into the mobile Drilling Information System database, from where it could be accessed semi-automated to produce digital lithologic columns using Strater 5 software (by Golden Software). The dataset is accompanied by a composite plot of core images acquired by optical line scanning. For the original images see corresponding data set extquotesingleLine scan images of IODP Hole 389-M00## extquotesingle. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025